The unwilling umpire - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2004)
When the umpire at the baseball game fundraiser is accused of stealing a collection of autographed baseballs, Dink, Josh, and Ruth Rose try to prove his innocence.
"A Stepping Stone book."
Keywords: Baseball stories; Sports stories; Baseballs -- Fiction; Baseball -- Fiction; Mystery and detective stories